Cellular gene expression in papillomas of the choroid plexus from transgenic mice that express the simian virus 40 large T antigen. - Marks, J R (1989)
Transgenic mice that contain the simian virus 40 (SV40) enhancer-promoter and large tumor (T) antigen gene develop papillomas of the choroid plexus. The tumors remain well differentiated on histological examination and express normal levels of tissue-specific mRNAs for transthyretin (TTR) and the 5-HT1C serotonin receptor, two differentiated cell markers. Both Northern (RNA) blot analysis and in situ cytohybridization have been used to monitor the steady-state levels of the mRNAs from the viral oncogene (T antigen) and from several cellular oncogenes. In situ hybridization demonstrated, in serial sections, increased levels of both T antigen mRNA and p53 mRNA localized in the tumor tissue but not in the normal brain tissue. The ratios of the steady-state levels of mRNA for p53/TTR and p53/L32, a ribosomal protein gene, were 2- to 20-fold higher in the tumor tissue than in the normal choroid plexus tissue. Several other oncogenes did not show elevated levels of mRNA in these tumors. p53 protein levels were not detectable in normal brain tissue, but p53 levels were very high in tumor tissue in which all of the p53 was found in a complex with the SV40 large T antigen. These data continue to show a close relationship between SV40 T-antigen-mediated tumorigenesis and the role of p53 in these tumors.